Interview with Maestro Renato Bruson, Conducted During the Masterclass in Parma (October 25-28, 2024) - Sergiu GARABAJII (Studia Universitatis Babeş-Bolyai. Musica, 2025)
This interview with Maestro Renato Bruson was conducted during a masterclass at his house-museum in Parma in October 2024. Bruson, one of the greatest baritones of the 20th century, is celebrated for his expressive singing and deep respect for the interpretative power of the word. Despite humble beginnings and no early access to music education, he rose to international fame with his debut in Verdi’s Il trovatore and later at the Metropolitan Opera. He credits his success to his dedication, seriousness, and his chamber music training under Professor Elena Fava Ceriati, which refined his interpretative sensibility. Bruson emphasized humility, consistency, and the avoidance of shortcuts in a singer’s journey. He warned against the negative influence of the media on young artists and stressed the importance of respecting one’s own vocal limits. For him, vocal technique, emotional depth, and the ability to move the audience are central to true artistry. He does not believe in predefined national schools of singing but sees taste and style as cultural variations. His message to future generations is simple yet powerful: “Study, study, study.”